Rancang Bangun Aplikasi Surat Pada Sub Bagian Komunikasi Pimpinan Bagian Protokol Dan Komunikasi Pimpinan Asisten Administrasi Umum Sekretariat Daerah Kabupaten Majalengka - Elawati; Ardi Mardiana (Universitas Majalengka, 2021)
The purpose of this research is to make a letter application to provide convenience to the manager of the manuscript in the Sub Division of Administration of the General Section of the General Administration Assistant of the Regional Secretariat of Majalengka Regency. This application is used for mail data management. The research methodology used in making this application is the XP (Extreme Program) method. Meanwhile, for making application interfaces using XAMPP software with the Bootstrap CSS framework and PHP Codeigniter framework with the MVC model (Model, View, Controller). The results of letter management with this application can print blank disposition sheets, letter data reports and can store files and letter data more properly in the storage directory. Applications made are based on the process of managing letters in the Sub Division of Administration Head of General Administration Assistant for General Administration of the Regional Secretariat of Majalengka Regency. This research is expected to be able to assist manuscript management in managing, filing and searching letters quickly, precisely and accurately.